2022
DOI: 10.3389/fresc.2022.997531
|View full text |Cite
|
Sign up to set email alerts
|

tDCS over the left prefrontal Cortex improves mental flexibility and inhibition in geriatric inpatients with symptoms of depression or anxiety: A pilot randomized controlled trial

Abstract: BackgroundPatients with depression and/or anxiety are commonly seen in inpatient geriatric settings. Both disorders are associated with an increased risk of cognitive impairments, notably in executive functioning. Transcranial direct current stimulation (tDCS), a type of non-invasive brain stimulation, involves the administration of a low-dose electrical current to induce neuromodulation, which ultimately may act on downstream cognitive processing.ObjectiveThe purpose of this study was to determine the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
(75 reference statements)
0
0
0
Order By: Relevance
“…About tDCS, we reported potentials good effects in reduc-reducing negative outcomes associated with older depression, such as cognitive dysfunction [45] and mood problems [47] whereas one work did not find significant improvements from tDCS in working and cognitive function [46]. In older people with functional limitations, tDCS has been proved to improve executive functions and dual tasking [57].…”
Section: Scibase Neurologymentioning
confidence: 99%
See 1 more Smart Citation
“…About tDCS, we reported potentials good effects in reduc-reducing negative outcomes associated with older depression, such as cognitive dysfunction [45] and mood problems [47] whereas one work did not find significant improvements from tDCS in working and cognitive function [46]. In older people with functional limitations, tDCS has been proved to improve executive functions and dual tasking [57].…”
Section: Scibase Neurologymentioning
confidence: 99%
“…Participants were divided in two groups: the one receiving anodal (n=10, M=6, F=4, mean age=77,10±6,98), while the second (n=10, M=4, F=6,mean age=72,50±7,46) sham tDCs over the left dorsolateral prefrontal cortex. It was reported that tDCS increases inhibitory processing and cognitive flexibility in the anodal tDCS group, whereas no relevant changes in attention or working memory measurements were observed [45]. A similar work analyzed 33 participants with previous single or recurrent episodes of MDD, evaluated through the SCID-IV and MADRS.…”
Section: Tdcs In Geriatric Depressionmentioning
confidence: 99%